2019
DOI: 10.1002/jum.14969
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the Elasticity of Hip Muscles and the Hip Migration Index in Cerebral Palsy

Abstract: Objectives-Cerebral palsy (CP) increases the risk of hip displacement during childhood. Abnormal hip muscle forces have been proposed as the predisposing factors. In CP, the amount of hip displacement is commonly evaluated by the Reimers hip migration index (MI) on an anteroposterior pelvic radiograph. To the best of our knowledge, the association between the elasticity of hip muscles measured by shear wave elastography and the MI has not been studied yet. Herein, we aimed to analyze the correlation between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Analan et al . found a weak correlation between the MI and other hip muscles ( 17 ) . In the present study, we identified a weak correlation between the FAA and other hip muscles.…”
Section: Discussionmentioning
confidence: 95%
“…Analan et al . found a weak correlation between the MI and other hip muscles ( 17 ) . In the present study, we identified a weak correlation between the FAA and other hip muscles.…”
Section: Discussionmentioning
confidence: 95%
“…To test the hypothesis that hyperactivity and spasticity of the hip abductors and flexors result in the hip displacement in CP, Doruk Analan et al analysed the correlation between the Reimers hip migration index and the elasticity of the mentioned muscles on SWE. No significant correlation was found [37].…”
Section: Cerebral Palsymentioning
confidence: 85%
“…Many soft tissues such as tendons, muscles, and fascia in the human body have begun to be examined with this technique. [ 13 , 25 , 26 ] Many studies have examined structural changes in skeletal muscle using the elastography technique, particularly hip muscles in patients with CP. Vola et al[ 14 ] found that the soleus muscle was more rigid in patients with CP.…”
Section: Discussionmentioning
confidence: 99%
“…Elastography, on the other hand, is a low cost, fast, non-invasive US-based application that allows quantitative evaluation of the properties of soft tissues, such as stiffness and flexibility. [9][10][11][12][13] Although there are several different elastography techniques, the most commonly used techniques sonoelastography, real-time elastography and shear wave, also known as realtime elastography. Shear wave elastography (SWE) is an objective method that quantitatively interprets muscle and tendon structures independently from the radiologist.…”
mentioning
confidence: 99%